Study on braided textile composites for sports protection - Wang, Chen (2018)
Braided textile reinforced composites become increasingly attractive as protection materials in sports (e.g. hockey sticks, helmets and shin guard) due to their high structural stability and excellent damage tolerance. There are requirements to develop an effective way to enhance product optimisation, test and design; however, the mechanical behaviours and energy dissipation mechanisms of braided composites have not been fully understood. There are no numerical modelling paradigms which are widely accepted due to the sheer complexity of the problem. Therefore, the aim of this thesis is to build a robust multi-scale modelling framework which will account for damage in the composite under static and dynamic loading states. Validated with corresponding experiments, the modelling capability should finally allow us to design braided composite structures for targeted performance before they are manufactured. In this thesis, the multi-scale pyramid of modelling braided textile composites was built up from micro-scale model, consisting with individual fibres, epoxy matrix and their interfaces. Material properties of these constituents, regarded as the most fundamental inputs, were characterised experimentally. The obtained results not only provided reliable references for further investigation of the carbon fibre and fibre/epoxy interface, but also delivered precise material inputs to the micro-scale model, which was successfully set up to compute three-dimensional strengths and moduli of fibre yarns. Then, the virtual descriptions of the interlaced geometries of braided composites were developed in a meso-scale model. Employing the meso-scale unit cell, the non-linear mechanical response of bi-axial braided composites was predicted. Hashin’s 3D failure criteria and continuum damage mechanics applied in failure analysis were proved to be effective. This study also elucidated that, yarns suffered from continuous failure during axial tension, and the effects of matrix damage become prominent with an increase in the braiding angle, causing a decrease in ultimate strength and the Young’s modulus. In addition, explicit simulations were developed to study responses of braided composites to both single and repeated low-velocity impacts using ABAQUS/Explicit with the VUMAT subroutine in a macro-scale model. The simulated results were verified by original data from the drop-weight tests. By applying the simulation method, the load evolution, energy dissipation, delamination area and damage accumulation could be well predicted under dynamic loading. Meanwhile, the main damage mechanisms of braided composites were analysed, by means of Micro-CT scan, including micro-cracks, delamination, matrix failure, fibre breakage and, uniquely for the braided composites, inter-yarn debonding. The experiments also indicated damage accumulation of braided composites strongly depended on normalised impact energy. Finally, two case studies applying the multi-scale modelling approach were introduced to optimise energy-absorption and impact-attenuation performance of a shin-guard structure for sports application. The results showed that interfacial strength and fracture energy can be designed in an optimal zone to balance structural integrity and energy absorption of braided composites. Moreover, shin-guard structure with ±45° bi-axial braided composite layer had better performance than ±25° braided structures. Two case studies demonstrated that the developed multi-scale modelling approach was effective for sports-product design. The performance of braided composites could be predicted by modifying features of constituents, instead of experimental attempts. Conversely, numerical results provided guidelines for optimisation of structures and properties of constitutive material in different length scales.